Present status of research and Development and institutional considerations for animal production system in the Asia-Pacific region - Devendra, C. (Japanese Society of Zootechnical Science, 1996)
This paper addresses the present status of research and Development in animal production; challenges for research in animal production systems including integrated natural resource management and use and the Development of sustainable agriculture; and institutional limitations and capacity to meet the changing needs and the new challenges. Partnerships between NARS and IARC's in animal production systems research is discussed at the end of the paper.